Management of Giant Gastric Ulcer Perforation: Report of a Case and Review of the Literature - Nitin Vashistha; Dinesh Singhal; Gurpreet Makkar; Suneel Chakravarty; Vivek Raj (Case Reports in Surgery)
Giant gastric ulcer (GGU) is defined as an ulcer more than 3 cm in diameter. Now infrequent in clinical practice, in the pre-H2 receptor antagonist (H2RA) era, the incidence of GGU varied between 12 and 24% of all gastric ulcers. Proton pump inhibitors reportedly achieve better healing rates and symptom relief in comparison to H2RA. The GGU is associated with high incidence of serious complications such as hemorrhage. A perforated GGU though rare (<2%) offers serious challenges in management. We report one such case wherein the role of multidetector CT scan (MDCT) for diagnosis and treatment planning, surgical options for GGU perforations, and factors affecting outcome are discussed.